Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Appendix B - Exercise Set: 28

Answer

$h = 1$

Work Step by Step

$\frac{2+h}{9} + \frac{h - 1}{3} = \frac{1}{3}$ Step 1: Clear the equation from fractions. $9(\frac{2+h}{9} + \frac{h - 1}{3}) = 9(\frac{1}{3})$ Step 2: Use the distribute property. $2+h + 3(h-1) = 3$ $2+h + 3h-3 = 3$ Step 3: simplify each side of the equation by combining like terms. $4h - 1= 3$ Step 4: The equation is linear. $4h - 1= 3$ Step 5: Get all variable terms on one side and all numbers on the other side by using the addition property of equality. $4h - 1 + 1 = 3 + 1$ $4h =4$ Step 6: Get the variable alone by using the multiplication property of equality. $4h \times \frac{1}{4} = 4 \times \frac{1}{4} $ $h = 1$ Final Step: Check each solution in the original equation. $\frac{2+1}{9} + \frac{1 - 1}{3}= \frac{3}{9} + \frac{0}{3}= \frac{1}{3}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.